Предмет: Алгебра,
автор: anyutk95
(х+6)²=(х+9)²
(х+6)²+(х+3)²=2х²
Ответы
Автор ответа:
0
x²+12x+36+x²=x²+18x+81
x²+12x-x²-18x=81-36
-6x=45
x=-7.5
x²+12x+36+x²+6x+9=2x²
x²+12x+x²+6x-2x²=-36-9
18x=-45
x=-2,5
x²+12x-x²-18x=81-36
-6x=45
x=-7.5
x²+12x+36+x²+6x+9=2x²
x²+12x+x²+6x-2x²=-36-9
18x=-45
x=-2,5
Похожие вопросы
Предмет: Английский язык,
автор: amirsanguliya
Предмет: Математика,
автор: piolol407
Предмет: Русский язык,
автор: feddersh
Предмет: Физика,
автор: dianka010203
Предмет: Алгебра,
автор: masha555masha